Exploring the beneficial effects of GHK-Cu on an experimental model of colitis and the underlying mechanisms - Shuzhen Mao; Jiahui Huang; Junyan Li; Fang Sun; Qilian Zhang; Qing Cheng; Wei Zeng; Dongya Lei; Shiyan Wang; Jing Yao (Frontiers in Pharmacology)
IntroductionUlcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) characterized by mucosal damage and impaired epithelial barrier function. While glycyl-l-histidyl-l-lysine-copper (GHK-Cu) exhibits known anti-inflammatory properties, its therapeutic mechanisms in UC remain undefined. This study was designed to systematically evaluate the therapeutic potential of GHK-Cu in a dextran sulfate sodium (DSS)-induced murine model of UC, with particular emphasis on elucidating its regulatory effects on the NAD-dependent deacetylase sirtuin-1 (SIRT1)/signal transducer and activator of transcription 3 (STAT3) signaling pathway.MethodsUC was induced in BALB/c mice with 3% DSS for 14 days. The protein expression levels of tight junction associated protein-1 (ZO-1), Occludin, inflammatory factors interleukin (IL)-6, IL-1β and tumor necrosis factor (TNF)-α, SIRT1, STAT3, p-STAT3, and retinoic acid receptor-related orphan receptor gamma t (RORγt) were detected by Western blot. Histopathological changes were evaluated by Hematoxylin and Eosin (H&E) and Alcian blue-periodic acid-Schiff (AB-PAS). Network pharmacology and molecular docking were used to predict the core targets of GHK Cu in the treatment of UC. An in vitro UC model was also established in mouse peritoneal macrophages (MPMs) using lipopolysaccharide (LPS), and a co culture model was constructed using mouse colonic epithelial cells (MCECs) and MPMs to examine the role of GHK Cu in promoting mucosal healing. STAT3 was silenced by gene transfection technology to verify the core role of STAT3 in GHK Cu treatment of UC.ResultsGHK-Cu alleviated weight loss, improved the disease activity index (DAI), reduced colonic edema and shortening, attenuated inflammatory damage, increased goblet cell numbers, suppressed inflammatory cytokines such as TNF-α, IL-6, and IL-1β, and promoted mucosal repair. Additionally, a co-culture system of MCECs and MPMs revealed that GHK-Cu facilitated MCECs healing, impaired by DSS, by upregulating ZO-1 and Occludin expression. Subsequently, network pharmacology and molecular docking identified SIRT1 as a potential target of GHK-Cu. Results showed that GHK-Cu upregulated SIRT1 protein expression and suppressed the expression of phosphorylated p-STAT3 in colon tissue and MCECs of the co-culture model. Our findings revealed that after transfection with STAT3-targeting siRNA (siSTAT3), the stimulant effect of GHK-Cu on the healing of MCECs and the effect on the protein expression of ZO-1 and Occludin is canceled. Nevertheless, after transfection with siSTAT3, it could inhibit the expression of inflammatory factors in conjunction with GHK-Cu. Furthermore, we found that GHK-Cu could inhibit RORγt expression in the colon tissue of UC mice.DiscussionThis study found that GHK-Cu demonstrated significant therapeutic effects in DSS-induced UC in mice. GHK-Cu may promote mucosal healing and enhance tight junction protein expression by regulating the SIRT1/STAT3 pathway. In addition to suppressing p-STAT3 expression, GHK-Cu may utilize additional pathways to inhibit inflammatory factors. Furthermore, GHK-Cu may reduce the number of Th17 cells. In summary, GHK-Cu may treat UC by acting on the SIRT1/STAT3 pathway.